A dual‐band case‐printed planar inverted‐F antenna design with independent resonance control for wearable short range telemetric systems. Issue 8 (13th April 2019) - Bouazizi, Amal; Zaibi, Ghada; Iqbal, Amjad; Basir, Abdul; Samet, Mounir; Kachouri, Abdennaceur
Abstract: In this article, a novel 3D meandered planar inverted‐F antenna (PIFA) is proposed for dual band application targeting Wireless Body Area Network (WBAN). The proposed antenna is printed on the casing of a 3D‐base‐station model having a size of 88 × 95 × 10.2 mm 3 . The proposed PIFA covers two bands including medical implant communication service (MICS) (402‐405 MHz), as well as the industrial, scientific, and medical (ISM) (2.4‐2.48 GHz) bands. Each of the two bands can be controlled independently. The 3D configuration contains two linked meandered resonators to downsize the structure. Due to its conformal shape, omnidirectional radiation pattern, and low‐profile nature, the proposed PIFA is a potential candidate for targeting the WBAN applications. The proposed antenna, covering the MICS and ISM bands, works with an optimally matching (VSWR<2) at the aforementioned bands. The design concept was validated by fabricating the antenna prototype and measuring its characteristics.